Imaginative Consciousness in the Creative Process of Adult Fiction Writers for Understanding the Role of Popular Culture - Helmanto, Fachri; Boeriswati, Endry; Anoegrajekti, Novi (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
The creative process of adult fiction writers often unfolds without a clear understanding of how imagination operates—both consciously and unconsciously. Yet storytelling emerges from a complex interplay between personal experiences and the symbolic pressures of surrounding popular culture. This study addresses the need to examine how imaginative consciousness is shaped, activated, and influenced by cultural environments in the writing practices of Indonesian authors. Using a narrative-phenomenological approach, the study explores the lived experiences of six writers active across digital and print platforms. The findings reveal two dynamic modes of imaginative consciousness: reflective and affective. In the reflective mode, writers engage in deliberate planning and narrative structuring; in the affective mode, imagination flows through memories, moods, and unconscious emotional cues. Popular culture consumption—such as online novels, market trends, and digital platforms—serves as both stimulus and narrative resource. This study offers a new understanding of imaginative consciousness as a flexible and adaptive cognitive process, where imagination becomes both a creative instrument and a medium for negotiating between self-identity and cultural symbols. It contributes to the theoretical development of imagination studies in contemporary Indonesian literature.